Characterization of feeding damage by tea mosquito bug, Helopeltis theivora Waterhouse (Hemiptera: Miridae) on Hainan Dayezhong tea cultivar - Yao, Qi; Lin, You-Ze; Qin, Shuang; Lin, Zhu-Feng; Ji, Xun-Cong (Frontiers in Plant Science, 2025)
The tea mosquito bug, Helopeltis theivora Waterhouse (Hemiptera: Miridae), is a devastating piercing-sucking pest in tropical tea plantations. The Hainan Dayezhong (HNDYZ) is a large-leaf tea cultivar widely cultivated around the Hainan tea region in South China. However, information regarding the feeding damage of H. theivora on the HNDYZ tea plant remains scarce. Here, we first describe the morphology of H. theivora in Hainan tea region. Subsequently, we investigate the feeding biology of H. theivora on HNDYZ tea shoots under laboratory conditions. Additionally, we survey the infestations of H. theivora in a small-leaf Jinxuan tea plantation and three large-leaf HNDYZ tea plantations under varying shaded conditions. The results indicated that the morphological features of eggs, nymphs, and adults of H. theivora in the Hainan tea region were similar to those of the same species reported in other tropical tea regions. Nymphs and adults of H. theivora primarily fed on tender leaves and produced a subcircular spot within 2 to 4 minutes. This feeding spot would gradually turn dark brown within 24 hours. Furthermore, the adjacent scattered spots would connect after 48 hours, resulting in a necrotic patch on the leaves by 72 hours. The peak feeding time for H. theivora occurred at night, specifically from 7:00 PM to 1:00 AM. The most preferred feeding site was at the second leaf position, accounting for 70.94 ± 3.68% of daily feeding spots. During the feeding peak, adults H. theivora produced more feeding spots than nymphs, with females and 5th-instar nymphs creating the largest feeding areas among all life stages. Field investigations showed that damage caused by H. theivora on the large-leaf HNDYZ tea cultivar was significantly greater than that on the small-leaf Jinxuan tea cultivar. More serious infestations of H. theivora were observed in the high-shade HNDYZ tea plantation compared to the medium-shade and no-shade HNDYZ tea plantations. This suggests that the different tea cultivars and shade conditions in tea plantations may influence the population of H. theivora in the field. These findings provide new insights for further research related to the feeding strategy of H. theivora on the HNDYZ tea cultivar.